Nutrient Status of Bhata Soils - Verma, B. R.; Sharma, V. B. (Indian Forester, 1989)
Chemical and physical nature of the bhata waste soils from protected and unprotected sites of Raipur, 21Â°14'N and 81Â°38'E) were studied. The upper layer (0-10 cm) of soils were gravelly loam-sand while gravelly sand-loam occurred at 10-20 and 20-30 cm depths. Available form of nitrogen content differed significantly among months at the protected site only. Though available phosphorus and potassium contents differed significantly among months at both sites, only available form of phosphorus indicated seasonal variations. Available form of potassium did not show a specific trend of decrease or increase as did nitrogen and phosphorus. Bhata waste soils of Raipur exhibit a slightly acidic reaction. The lowest pH at both sites was found during the dry period. The pH indicated decreasing trend with depth. The low productivity of bhata wastelands may be attributed to the physico-chemical nature of the soil.